THE EFFECTIVENESS OF LONG FERMENTATION OF COCONUT DRUGS IN FEED ON THE GROWTH OF TILA FISH (Oreochromis niloticus) - Muslim; Arisa, Iko Imelda; Dewi, Cut Dara (Journal of Aquaculture and Fish Health, 2025)
This study aims to determine the effect of fermentation time on coconut dregs using yeast in tilapia (Oreochromis niloticus) feed on absolute length, absolute weight, specific growth rate (SGR), Feed Conversion Ratio (FCR), feed efficiency (FE) and Survival Rate (SR). The research method used in this study was a completely randomized design (CRD) with 5 treatments and 4 replications. Treatments consist of A (coconut dregs without fermentation), B (coconut dregs fermented for 2 days), C (coconut dregs fermented for 4 days), D (coconut dregs fermented for 6 days) and E (coconut dregs fermented for 8 days) . The test fish used were tilapia fry (Oreochromis niloticus) which were reared for 40 days with feeding at 08.00 WIB, 13.00 WIB, 18.00 WIB. The length of fermentation of coconut dregs had an influence (P<0.05) on the growth of tilapia, including growth in absolute length, absolute weight, SGR, FCR and FE, but did not have an influence (P>0.05) on SR of tilapia. The best results were found in treatment D with absolute length growth of 2.80 cm, absolute weight of 3.27 g, SGR of 0.082%/day, FCR of 1.06, FE of 94.64% and SR of 95%.